Multi-fidelity modelling of a high bypass ratio turbofan engine with variable area nozzle - Andrea Magrini; Ernesto Benini (Propulsion and Power Research)
Low pressure ratio fans of modern civil turbofans suffer from reduced stall margin in the take-off operating line and at part-speed, requiring variable geometry devices. Variable area nozzles (VAN) are one of the investigated solutions to control engine operating conditions throughout the mission. In this paper, we present a multi-fidelity modelling approach for an ultra-high bypass ratio turbofan engine with a VAN, combining a zero-dimensional thermodynamic cycle simulator using a realistic fan map with two- and three-dimensional detailed computational fluid dynamics (CFD) simulations for internal/external flow coupling. By adopting a novel algorithm to match the cycle conditions to the CFD solutions, the propulsive performance of the turbofan is analysed in a reference aircraft mission. The numerical method captures the effect on thrust generation and nacelle drag, providing a more reliable estimation of the impact of VAN on engine operation and efficiency. Low-speed mission points are confirmed to be those that benefit the most from an enlarged fan nozzle area, with a possible improvement of 3% in terms of thrust and specific fuel consumption at take-off and approach using a 10% larger area, similarly predicted by both 2D and 3D models. A preliminary acoustic evaluation based on semi-empirical noise models indicates a modest effect on noise emissions, with up to 1 dB reduction in microphone signature at the sideline for a nozzle area increased by 10%.